Composition and Diversity Of Oysters (Crassostrea) In The Mangrove Ecosystem Area, Gampong Ruyung, Mesjid Raya District, Aceh Besar Regency - Intan Mutia; Asiah M.D Asiah M.D; M. Ali Sarong; Devi Syafrianti; Safrida Safrida (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2022)
Mangrove forest or mangrove forest is a forest that grows in brackish water and is influenced by the tides of sea water. Mangrove forests are usually inhabited by various types of aquatic biota such as fish, crabs, shrimp, shellfish and oysters. The purpose of the study was to determine the Species Composition and Diversity of Oysters (Crassostrea) based on the substrate, and aquatic environmental factors in the Ruyung Mangrove Area, Mesjid Raya District, Aceh Besar District. This research was conducted in the Ruyung Mangrove Ecosystem Area, Mesjid Raya District, Aceh Besar District. Data collection November - December 2020. The method in this study is a survey method with purposive sampling technique. The data is calculated using the composition formula and diversity formula. The results of the study found 5 species of oysters from two orders, namely Ostreida and Pterioida. The dominant species is Crassostrea gigas with a total of 6,224 individuals. The least numerous species is Crassostrea virginica with 1,245 individuals. The composition of oyster species in the Ruyung Aceh Besar Mangrove Ecosystem, namely Crassostrea gigas, has a composition of 0.48% (medium category). Crassostrea angulata 10%, Crassostrea virginica 10%, Crassostrea rhizophorae 22%, and Isognomon alatus 11% belong to the low category. Oyster diversity in the Ruyung Mangrove Ecosystem is low, with a diversity index of each species, namely Crassostrea gigas (H=0.35), Crassostrea angulata (H=0.23), Crassostrea virginica (H=0.23), Crassostrea rhizophorae (H=0,33), and Isognomon alatus (H=0,11). The conclusion is that the species composition of oysters in the Ruyung Mangrove Ecosystem is categorized from medium to low, and the diversity of oysters is low.Keywords: Composition, Diversity, Oyster, Mangrove EcosystemHutan mangrove atau hutan bakau adalah hutan yang tumbuh di air payau dan di pengaruhi oleh pasang surut air laut. Hutan mangrove biasanya dihuni oleh berbagai jenis biota perairan seperti ikan, kepiting, udang, kerang dan juga tiram. Tujuan Penelitian untuk mengetahui Komposisi Spesies dan Diversitas Tiram (Crassostrea) berdasarkan substrat, dan faktor lingkungan perairan di Kawasan Mangrove Ruyung Kecamatan Mesjid Raya Kabupaten Aceh Besar. Penelitian ini dilakukan di Kawasan Ekosistem Mangrove Ruyung Kecamatan Mesjid Raya Kabupaten Aceh Besar. Pengambilan data November - Desember 2020. Metode dalam penelitian ini adalah metode survey dengan teknik purposive sampling. Data di hitung menggunakan rumus komposisi dan rumus keanekaragaman. Hasil penelitian ditemukan 5 spesies tiram dari dua ordo yaitu Ostreida dan Pterioida. Spesies yang mendominasi yaitu Crassostrea gigas dengan jumlah 6.224 individu. Spesies yang paling sedikit jumlahnya yaitu Crassostrea virginica dengan jumlah 1.245 individu. Komposisi spesies tiram di Ekosistem Mangrove Ruyung Aceh Besar yaitu Crassostrea gigas komposisi 0,48% (kategori sedang). Crassostrea angulata 10%, Crassostrea virginica 10%, Crassostrea rhizophorae 22%, dan Isognomon alatus 11% tergolong kategori rendah. Diversitas tiram di kawasan Ekosistem Mangrove Ruyung tergolong rendah, dengan indeks Diversitas dari masing-masing spesies yaitu Crassostrea gigas (H=0,35), Crassostrea angulata (H=0,23), Crassostrea virginica (H=0,23), Crassostrea rhizophorae (H=0,33), dan Isognomon alatus (H=0,11). Kesimpulannya adalah Komposisi spesies tiram di Ekosistem Mangrove Ruyung termasuk kategori dari sedang hingga rendah, dan Diversitas/Keanekaragaman tiram tergolong rendah.Kata kunci: Komposisi, Diversitas, Tiram, Ekosistem Mangrove.